Power management system for hybrid AC/DC microgrid based on high frequency isolated interlink converter. Issue 1 (March 2020) - Linn, Zarchi; Win, Soe
Abstract: The hybrid AC/DC microgrid systems have been popular and being developed as the next generation power systems because of the comprehensive combination of both AC and DC microgrid systems. Power management scheme is one of the most critical operation aspects for hybrid microgrids because the system is operating with various generation sources and loads such as renewable energy sources, energy storage systems and AC and DC loads. Therefore, in this research, control strategies and power management scheme is considered for all possible operation modes of standalone and grid-connected conditions. In the existing microgrid system in Electrical Power Engineering department in Yangon Technological University, rooftop PV plant and battery are cooperating to supply the electricity. The inverter in this system allows the unidirectional power flow from DC to AC and there is no specific power management system for grid-connected and standalone operation mode. To provide bidirectional power flow in the existing system, the configuration of converter and control strategies for power management system are developed in this research. To provide the bidirectional power flow between AC bus and DC bus, the bidirectional interlink power converter with high frequency isolation is applied. The control system including the power balancing between generation and demand, DC link voltage control and AC link voltage and frequency control is considered. By applying droop control method in the developed system, power flow balancing between AC bus and DC bus is maintained. And also, using high frequency isolation transformer in interlink converter provides fast response of the system performance and maintaining continuous power supply within each AC system and DC system during disturbance condition in one subsystem. The performance of the proposed power management system is demonstrated by using MATLAB/Simulink.